2012
DOI: 10.1111/ijcp.12026
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of homeopathy: a systematic review of published case reports and case series

Abstract: Summary Aim:  The aim of this systematic review was to critically evaluate the evidence regarding the adverse effects (AEs) of homeopathy. Method:  Five electronic databases were searched to identify all relevant case reports and case series. Results:  In total, 38 primary reports met our inclusion criteria. Of those, 30 pertained to direct AEs of homeopathic remedies; and eight were related to AEs caused by the substitution of conventional medicine with homeopathy. The total number of patients who experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 39 publications
(108 reference statements)
0
62
1
9
Order By: Relevance
“…The results of Curcani and Tan study confirmed its effect on uremic pruritus (16), whereas the systematic review by Posadzki et al reported mild to severe adverse effects of aromatherapy, with dermatitis mentioned as the most common side effect. Mortality was reported in another study (17). In contrast, no allergic reactions or deaths have been reported thus far with the use of cool dialysate.…”
Section: Discussionmentioning
confidence: 86%
“…The results of Curcani and Tan study confirmed its effect on uremic pruritus (16), whereas the systematic review by Posadzki et al reported mild to severe adverse effects of aromatherapy, with dermatitis mentioned as the most common side effect. Mortality was reported in another study (17). In contrast, no allergic reactions or deaths have been reported thus far with the use of cool dialysate.…”
Section: Discussionmentioning
confidence: 86%
“…Clearly, numerous homeopathic treatments use known poisonous plant and animal sources [38]. Consistent with this, ultramolecular preparations are necessary for patient's safety [38,39]. Hence it is biologically plausible that ultramolecular, non-succussed preparations are sufficient to produce cellular response, as indicated from in vitro studies of Arsenicum album 6CH, 30Ch, and 200CH on the MT4 continuous cell line [40].…”
Section: Homeopathy's Adverse Effectsmentioning
confidence: 98%
“…Homeopathic treatments containing allergenic conventional medications without disclosure to the consumer have been voluntarily withdrawn from the United States market [37]. Clearly, numerous homeopathic treatments use known poisonous plant and animal sources [38]. Consistent with this, ultramolecular preparations are necessary for patient's safety [38,39].…”
Section: Homeopathy's Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore homeopathy is accused to be of being a humbug, a placebo. Many publications describe very critical [1,2] and many publications describe successful homeopathy [3,4]. For years many theories have…”
Section: Introductionmentioning
confidence: 99%